Repairment of Planetary Carrier of Roller Press Planetary Reducer - Liu Qiang; Tan Yinglin; Zhang Hao; Li Simin (Jixie chuandong)
The disassembly of the planetary carrier of a roller press planetary reducer is easy to cause damage to the hollow output shaft. Aiming at the repair of the damaged planetary carrier,a bilateral board planetary carrier is brought up. The repair scheme is proposed,the 3D modeling of the damaged planetary carrier is carried out by using Solid Works and using the simulation part of the software,the stress and displacement of the carrier are analyzed. The results show that,the maximum stress of the repaired planetary carrier is 306. 7 MPa,the relative displacement of the pin hole of planet wheel is 0. 09 mm. This result is able to satisfy the request of the strength and stiffness of planetary carrier. On conclusion,this repair scheme can meet the use requirement in practice.